Spatial Distribution Characteristics of Microplastics in Multiple Types of Beach Sediments in Pearl River Estuary - LI Zhen; YUAN Bing; CHEN Zhihe (Renmin Zhujiang)
Estuarine beaches are one of the important pools of microplastics, while the distribution characteristics of microplastics at different depths in various types of beach sediments in the Pearl River estuary still need in-depth study. This study investigates the vertical distribution of microplastics and their spatial variation characteristics in different types of beaches in the Pearl River estuary. The sandy beaches of Tangjiawan Beach and Jinsha Beach and the mangrove forest of Qi'ao Island in Zhuhai are selected as examples. A total of 57 sediment column samples are collected, and microplastics in different sediment layers are analyzed in detail. The abundance of microplastics in the surface layer (0~5 cm) and deep layer (5~15 cm) of sediments is 1 107.6 and 821.94 n/kg from Tangjiawan beach, 694.0 and 457.0 n/kg from Jinsha Beach, and 835.0 and 556.7 n/kg from the mangrove forest of Qi'ao Island, respectively. The average abundance of microplastics in the deeper layer (15~45 cm) of the mangrove forest of Qi'ao Island is 302.6 n/kg. The color of microplastics in beach sediments is statistically analyzed, and black is the most common color. In addition, the shapes of microplastics are mainly fiber and fragment, with fibers being the most common shape, and 0.315-0.500 mm being the most common size range of microplastics in these beaches. Cellophane and polyethylene are the two most common types of microplastics in these beaches. This study preliminarily reveals the characteristics of the vertical distribution of microplastics in the beaches of the Pearl River estuary, which provides an important basis for further developing scientific control strategies for microplastics in the beaches of the Pearl River estuary.